Eat this, not that! Restaurant survival guide : the no-diet weight loss solution - Zinczenko, David (Rodale, 2010)
Loaded with tips on everything from navigating neighborhood restaurant menus to making smart choices in the drive-thru to cutting cash and calories at the country's largest chain restaurants, Eat this, not yhat! Restaurant and fast-food survival guide is the indispensable encyclopedia to the world of eating out.